Ammonites from the Upper Cretaceous of West Greenland. - Birkelund, Tove (Meddelelser om Grønland, 1965)
Ammonites from Nûgssuaq and Svartenhuk, belonging to the genera Hypophylloceras, Saghalinites, Pseudophyllites, Baculites, Diplomoceras, Scaphites, Clioscaphites, Haresiceras and Borissjakoceras, are described. Baculites and Scaphites are richly represented, and the material provides a basis for evaluating the subgenera Hoploscaphites and Discoscaphites. The ontogeny and the phylogeny of most of the genera are discussed and juvenile stages of Saghalinites and Scaphites described. Eleven new species and three new subspecies are introduced. The stratigraphical, palaeogeographical and palaeoecological aspects of the ammonite assemblages are considered, and a discussion of sexual dimorphism in Scaphites is given. The presence of 12 biozones from the Upper Turonian? , Coniacian, Santonian, Campanian and Maastrichtian is demonstrated. The stratigraphical correlation of European and North American Upper Cretaceous deposits is discussed and the West Greenland zones are correlated with North American and European ammonite zones. All the Upper Turonian ?-Santonian species have affinities with species endemic to the Western Interior of North America. One of the genera, Clioscaphites from the Santonian, occur only within that area. The Campanian scaphites and baculites are at first mostly like species from the Interior of North America, later, in the Upper Campanian, European affinities are more prominent. Haresiceras from the Lower Campanian is endemic to the Western Interior of North America. The Maastrichtian scaphites and baculites are closely related to endemic species from the Interior of North America, principally from the Fox Hills Formation of the type area. Hypophylloceras, Saghalinites and Pseudophyllites from the Campanian-Maastrichtian have Indo-Pacific relations and Diplomoceras may be related to European forms. The ammonites, together with the belemnites and inoceramids from the area, so far as they are identified, show that a sea-way to the north, through the Arctic Seas, connected this area with the Interior of North America from the Upper Turonian or Coniacian to the Maastrichtian. The area apparently was also connected with Europe by a sea-way during that part of the Upper Cretaceous. The occurrence of ammonites with Indo-Pacific affinities may further indicate the presence of a northern sea-way between the Pacific and the Arctic Seas during parts of the Campanian- Maastrichtian interval.